THE STUDENTS READING ANXIETY AND READING STRATEGIES AT SMP NEGERI 4 BAUBAU - Nety Nety; Rizal Arisman; Asti WahyuniB (English Education Journal, 2021)
The objective of the research was to examine students’ reading anxiety and students’ reading strategies to overcome reading anxiety at SMP Negeri 4 Baubau. Data Collection in this study was carried out using a research instrument in the form of questionnaires. There was research questionnaire “EFL Reading Anxiety Inventory (EFLRAI) consisting 23 items statements to find out the level of students’ reading anxiety. There was also reading strategies questionnaire which consists of 20 items statements to find out the students’ reading strategies. The data obtained were analyzed by using SPSS program 21.0. The results showed that students’ reading anxiety was in the high category with the mean score 2.75 which was dominated by top-down reading anxiety and bottom-up reading anxiety, while the reading strategy was in the moderate category by the mean score 2.81 and the dominantly used was metacognitive strategy.